Neural Control of Voluntary Eye Closure: A Case Study and an fMRI Investigation of Blinking and Winking - van Koningsbruggen, Martijn G. (Behav Neurol, 2012)
The current paper describes a rare case of a patient who suffered from unilateral apraxia of eye closure as a result of a bilateral stroke. Interestingly, the patient’s ability to voluntarily close both eyelids (i.e. blinking) was not affected, indicating that different neural mechanisms control each type of eye closure. The stroke caused damage to a large part of the right frontal cortex, including the motor cortex, pre-motor cortex and the frontal eye field (FEF). The lesion in the left hemisphere was restricted to the FEF. In order to further study the neural mechanisms of eye closure, we conducted an fMRI study in a group of neurological healthy subjects. We found that all areas of the oculomotor cortex were activated by both left and right winking, including the FEF, supplementary eye field (SEF), and posterior parietal cortex (PPC). Blinking activated FEF and SEF, but not PPC. Both FEF and PPC were significantly more active during winking than blinking. Together, these results provide evidence for a critical role of the FEF in voluntary unilateral eye closure.